(3JMdjd h JUeje fXe GdeYdheGJ (B/s - (3jGSjf, SYO ZGdHs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2010)
1)(3CfhGY fXe GdeYdheGJ GdeMhSHI (B: (3JWhQ fXe GdeYdheGJ , GdPcGA GdUfGYj , GdfXe GdNHjQI , JbfjGJ GdPcGA GdUfGYj GdCNQi , fXe GdeYdheGJ GdJfajPjI GdGSJQGJjLjI , (B2)(3fXe GdeYdheGJ aj efXeGJ GdCYeGd GdMOjKI (B: (3fXe GdeYdheGJ GdEOGQjI aj efXeGJ GdCYeGd , fXe GdeYdheG J GdEOGQjI h GdeSJhjGJ GdEOGQjI , fXe GdeYdheGJ GdEOGQjI ,(B3) (3fXQjI efgLjI Edi JMdjd h JUeje GdfXe (B: (3fXQjI GdfXe GdYGeI h JMdjd h JUeje GdfXe , GdeOGNd GdHOjdI dJUeje fXe GdeYdheGJ GdeMhSHI , efgLjI JWhjQ h JUeje fXe GdeYdheGJ , (B4) (3JbfjGJ JMdjd h JUeje GdfXe ,(B5) (3JUeje bGYOI GdHjGfGJ h THcGJ GdGJUGd ,(B6) (3WQb JMdjd h JUeje h JWhjQ fXe GdeYdheGJ GdGOGQjI (B.s
(3eQGLY U(B.390 (3;edGMb U(B.293 (3; bGFeI GdeUWdMGJ U(B.313s
Keywords: (3EOGQI GdGYeGds; (3GdMhGSjHs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s